Packet radio network for volcano monitoring an implementation on Taal (Philippines) - Machenbaum, Roland (Philippine Engineering Journal)
This paper describes an implementation of a packet radio network on Taal volcano. The network, based on amateur radio hardware and software, allows the Philippine Institute of Volcanology and Seismology (PHILVOLCS) to retrieve real time data from various instruments located on and around the volcano island. The actual list of instruments includes 10 digital seismic stations, 3 tiltmeters, 2 radon sensors, 1 geochemical station (water temperature and conductivity) and an acoustic station. The original features of the network are the use of only one radio frequency simplifying frequency allocation procedures and equipment management, redundancy allowing failures of nodes without loss of data, low power consumption reducing the cost of field power supplies. The network is linked to the internet by a radio link from PHILVOLCS to the University of the Philippines (UP). This link allows foreign organizations to access the data and provides basic internet services (mail, ftp, telnet...) to PHILVOLCS and any user located in the Taal vicinity.